Post-migration stress mediates associations between potentially traumatic peri-migration experiences and mental health among Middle Eastern refugees in Germany - El-Awad, Usama; Eves, Robert; Hachenberger, Justin; Bozorgmehr, Kayvan; Entringer, Theresa M.; Hecker, Tobias; Razum, Oliver; Sauzet, Odile; Lemola, Sakari (BMC public health, 2025)
Background: On their way to host countries, refugees are often exposed to severe adversity, including cumulative experiences of fraud, extortion, robbery, detention, and shipwrecks, as well as prolonged, life-threatening small boat crossings. However, little research has examined the long-term impact of such peri-migration stressors on subsequent stress and mental health after arrival. This study explored how cumulative exposure to potentially traumatic events (PTEs) and small boat crossings before arrival affected psychological distress in Middle Eastern refugees, considering the mediating role of post-migration stress in the years following resettlement in Germany. Methods: Longitudinal data from the IAB-BAMF-SOEP Survey of Refugees collected at three survey waves (2016, 2018, and 2020; N = 541, Mage = 38.77, 14% female) were analyzed using a causal mediation approach with linear mixed models. Self-reports of cumulative exposure to PTEs and small boat crossings in the Mediterranean indicated peri-migration stressors, while perceived discrimination and migration-related worries reflected post-migration stress. Psychological distress was assessed using a general health questionnaire. Results: PTEs were significantly associated with higher migration-related worries (β = 0.10, p < .001). Migration-related worries significantly mediated the association between PTEs and psychological distress (ACME = 0.02, 95% CI [0.01, 0.04], p < .001; ADE = 0.07, 95% CI [0.03, 0.11], p < .001). In contrast, perceived discrimination did not mediate this link. However, small boat crossings were significantly associated with higher perceived discrimination (β = 0.11, p < .001), which in turn mediated their association with psychological distress (ACME = 0.05, 95% CI [0.02, 0.08], p < .001), while the direct effect was non-significant. These indirect effects intensified over time. Conclusions: Peri-migration stressors may contribute to long-term mental health issues in refugees via their post-migration stress experiences. However, these mediation pathways may differ, underscoring the need for nuance and further investigation. Addressing both early traumatic experiences and post-migration adversities, such as discrimination and migration-related worries, is crucial to mitigating refugees’ long-term psychological distress. These findings highlight the importance of early prevention and intervention efforts that address post-migration stress as a key factor in reducing the long-term mental health burden among refugees.